Single Molecule Localization Microscopy of Mammalian Cell Nuclei on the Nanoscale - Szczurek, Aleksander; Xing, Jun; Birk, Udo J.; Cremer, Christoph (Frontiers in Genetics, 2016)
Nuclear texture analysis is a well-established method of cellular pathology. It is hampered, however, by the limits of conventional light microscopy (ca. 200 nm). These limits have been overcome by a variety of super-resolution approaches. An especially promising approach to chromatin texture analysis is single molecule localization microscopy as it provides the highest resolution using fluorescent based methods. At the present state of the art, using fixed whole cell samples and standard DNA dyes, a structural resolution of chromatin in the 50 - 100 nm range is obtained using single molecule localization microscopy. We highlight how the combination of localization microscopy with standard fluorophores opens the avenue to a plethora of studies including the spatial distribution of DNA and associated proteins in eukaryotic cell nuclei with the potential to elucidate the functional organization of chromatin. These views are based on our experience as well as on recently published research in this field.